Pengaruh Sistem Pembayaran E-Money Dalam Era Digital Di Tengah Wabah Covid-19 : Studi Kasus Pada Masyarakat Semarang - Yasinta Maulida Rohmah; Nila Tristiarini (ITB AAS INDONESIA, 2021)
The spread of the Corona virus is getting bigger and bigger, making people keep their distance from each other. Social distancing is the new rule from the government that people should adapt. It influences how people choose the electronic money to pay without contact each other. The use of electronic money led to the Cashless Society. This study aims to explain the effect of benefits, convenience, and security & risk effects on the e-money payment system in the digital era in the midst of the Covid-19 outbreak. This research is included in the primary research which includes 107 respondents. The analysis used is multiple linear regression analysis. The results of this study are that the perceived benefits and benefits variables partially have a positive and significant effect on the interest in using e-money, and the variables of trust and influence have a negative effect on the use of e-money.